2015
DOI: 10.4172/2165-8056.1000126
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Enzyme Production by Trichoderma asperellum for the Degradation of Duckweed

Abstract: The on-site production of cell wall degrading enzymes is an important strategy for the development of sustainable bio-refinery processes. This study concerns the optimization of production of plant cell wall-degrading enzymes produced by Trichoderma asperellum. A comparative secretome analysis was performed on T. asperellum growing on PDA agar, wheat bran and duckweed, respectively. T. asperellum proved to be able to produce a wide enzyme profile, including both depolymerization and debranching enzymes, mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Notwithstanding that xylanase is a principal fraction of several cell-walls degrading enzymes by which it exerts its mycoparasitic property, most studies on T. asperellum have focused on its bio-control ability at the expense of other industrial uses. Recently, both Bech et al (2015) and Marx et al (2013) separately reported a detailed proteomics of the secretome by T. asperellum to show xylanase as an important component enzyme that could be exploited for important industrial processes. However, despite their respective strides, the potential of T. asperellum as a suitable fungal isolate for enhanced xylanase has not been well exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding that xylanase is a principal fraction of several cell-walls degrading enzymes by which it exerts its mycoparasitic property, most studies on T. asperellum have focused on its bio-control ability at the expense of other industrial uses. Recently, both Bech et al (2015) and Marx et al (2013) separately reported a detailed proteomics of the secretome by T. asperellum to show xylanase as an important component enzyme that could be exploited for important industrial processes. However, despite their respective strides, the potential of T. asperellum as a suitable fungal isolate for enhanced xylanase has not been well exploited.…”
Section: Introductionmentioning
confidence: 99%
“…T. asperellum has been shown to produce hydrolytic enzymes such as cellulase and xylanase [2 , 3] . T. asperellum has also been reported to hydrolyse wheat bran, wheat straw, paper, sawdust, corncob, duckweed, and agave by secreting cellulases [2] , [3] , [4] , [5] , [6] , [7] . Strain PK1J2 has been proven to be capable of producing high cellulase.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Previous study found that T. asperellum T-1 could largely secrete β-1, 4-endoxylanase (Wang et al 2015), a kind of cellulase that cleaves the β-(1,4)glycosidic bonds between xylose units in the xylan backbone to produce xylo-oligosaccharides. Moreover, both Bech et al (2015) and Marx et al (2013) separately reported that xylanase secreted by T. asperellum could be exploited for important industrial processes as an important component enzyme. The promoter of the xylanase gene is a typical inducible strong promoter, which has been used to promote the expression of cellulase genes (Rahman et al 2009).…”
Section: Construction Of the Genetic Transformation System Of T Aspementioning
confidence: 99%
“…And there are few reports on improving cellulase activity of T. asperellum by using genetic modification. Among the limited publications, most are about the cloning and in vitro expression of single cellulase gene (Marcello et al 2010;Bech et al 2015), or intend to obtain high-yield cellulase mutants by physical mutagenesis (Raghuwanshi et al 2014). Therefore, this research aims to firstly construct an effective genetic transformation mediated by Agrobacterium tumefaciens AGL-1 and then to improve the cellulase activity of T. asperellum T-1 using molecular biological methods.…”
Section: Introductionmentioning
confidence: 99%